Long-Range, pH-Dependent Effects on the Carbon-13 Nuclear Magnetic Resonance Spectra of Oxytocin - Deslauriers, Roxanne (1974)
The effects of hydrogen ion concentrations on the carbon-13 nuclear magnetic resonance spectra of oxytocin were investigated. The starting pD of 3.0 was increased stepwise to 8.4. A change of the state of protonation of the N-terminal amino group of oxytocin is accompanied by changes in chemical shifts of carbon-13 nuclei of amino-acid residues located in the 20-membered ring of the hormone. The resonance positions of the acyclic peptide portion, Pro-Leu-Gly-NH(2), remain constant. The pD-induced chemical-shift changes of carbons up to five bonds removed from the site of protonation are interpreted in terms of “through-bond” and “through-space” mechanisms. Chemical-shift changes of carbons more than five bonds removed are proposed to have a conformational origin. It is suggested that a change in the charge density of the amino group perturbs the dihedral angle of the —CH(2)—S—S—CH(2)— moiety of oxytocin, which in turn significantly affects the overall conformation of the 20-membered ring of the hormone.